2010
DOI: 10.3889/mjms.1857-5773.2010.0096
|View full text |Cite
|
Sign up to set email alerts
|

<i>Bgl II</i> Polymorhism of the α2β1 Integrin Gene in Macedonian Population

Abstract: Background. Glycoprotein (GP) Ia/IIa or α2β1 integrin is a platelet receptor for collagen and it mediates platelet adhesion to vascular subendothelium and is involved in thromb formation. Genetic polymorphism of α2β1 known as Bgl II affects the density of platelet GP Ia/IIa receptor on the platelet surface. Recent studies had shown relationship between this polymorphism and the risk of myocardial infarction, stroke, as well as diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Therefore, they suggested that patients with BglII (+/-, +/+) genotypes might benefit from anti-platelet therapies. Similarly, Pavkovic et al [19] studied polymorphism in GP Ia gene and suggested an association with the variations in platelet α2β1 expression levels. They suggested that platelets from individuals with 807T allele have higher levels of α2β1 integrins as compared to individuals of 807C allele.…”
Section: Group-i Group-iimentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, they suggested that patients with BglII (+/-, +/+) genotypes might benefit from anti-platelet therapies. Similarly, Pavkovic et al [19] studied polymorphism in GP Ia gene and suggested an association with the variations in platelet α2β1 expression levels. They suggested that platelets from individuals with 807T allele have higher levels of α2β1 integrins as compared to individuals of 807C allele.…”
Section: Group-i Group-iimentioning
confidence: 94%
“…Variation in platelet GP density becomes a risk factor for haemostatic abnormalities [17] and this platelet α2β1 density is genetically determined [18]. Hereditary variation in platelet level of α2β1 integrin is defined by the existence of multiple alleles of α2 gene therefore it could have a significant impact on platelet function, contributing to an increased risk of thrombosis or bleeding in relevant disease states [19]. The same polymorphism has been studied by Matsubara et al [20] and Shi et al [21] in Japanese and Suzhou Han population respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Wide variations in pathopysiological processes involved in the density of a platelet collagen receptor (α 2 β 1 integrin or glycoprotein Ia/IIa) are reportedly associated with polymorphisms in the gene encoding the α subunit at the receptor 9. The aim of the study was to determine the relationship between the G894T polymorphism of the eNOS gene and the BgI II polymorphism of the ITGA2 gene and susceptibility to DR and to determine whether their genetic variants will affect the type of retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Several polymorphisms have been identified in the gene encoding the α2 subunit in the α2β1 integrin ( ITGA2 ). Among them, the BgI II polymorphism located in intron G is reported to be linked with two exonic polymorphisms, 807C and 873A (Kritzik et al, 1998) to affect the density of platelet receptors α2β1 (Pavkovic et al, 2010), thus contributing to the high risk of thrombosis. Indeed, the density of platelet α2β1 receptors is ruled by several polymorphisms in ITGA2 : Bgl II in intron G, 807T/C in exon 7 and 837T/C and 873A/G in exon 8 of the ITGA2 .…”
mentioning
confidence: 99%
“…Three α2 gene alleles are defined by these polymorphisms: allele 1 is governed by (807 T, 837 T, 873A) variants and linked to the Bgl II(+) allele and has been reported to be associated with high expression levels of α2β1 receptors, but the alleles 2 and 3 linked to (807C, 837T, 873G) and (807C, 837C, 873G) polymorphisms respectively and influenced by the Bgl II(−) allele were associated with low α2β1 receptors density (Kritizik et al, 1998). The Bgl II(+) allele has been considered a contributing factor to high level of α2β1 receptors and frequency of this polymorphism was reported to be 32% and 27% in healthy Macedonian and Chinese subjects (Pavkovic et al, 2010; Tsai et al, 2001) respectively. Otherwise, the α2 integrin polymorphism has been reported to be associated with the incidence of IS in young patients (Carlsson et al, 1999; Maakaroun et al, 2003).…”
mentioning
confidence: 99%